2019
DOI: 10.3390/su11061720
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Compounding Process for the Development of Eco-Friendly SCG/PP Composite Pellets

Abstract: As the consumption of coffee increases worldwide, the amount of spent coffee grounds (SCG) is gradually increasing every year. Some of these grounds are recycled for composting, but most are discarded, which causes widespread financial and social costs. We developed a bio-based plastic pellet by blending polypropylene (PP) with waste biomass SCG to convert it into a sustainable, recyclable eco-friendly material. It was confirmed that extrusion compounding for SCG/PP composite pellets and injection molding with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Many studies have investigated the pellet of coffee grounds and some have found slightly lower heating values (18.8 MJ/kg 50 , 19.6 MJ/kg 51 ) than that reported in this study while other report much higher heating values (23.4 MJ/kg 7 , 25.7 MJ/kg 52 ). Other studies have verified the pelletizing process through mixtures with other types of waste 53 or materials 54 , 55 , or with different percentages of moisture. Still others have modified other parameters such as die height, Lisowski et al (2019) 56 and have verified how the moisture of the matrix can be determined in the pelletizing process.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the pellet of coffee grounds and some have found slightly lower heating values (18.8 MJ/kg 50 , 19.6 MJ/kg 51 ) than that reported in this study while other report much higher heating values (23.4 MJ/kg 7 , 25.7 MJ/kg 52 ). Other studies have verified the pelletizing process through mixtures with other types of waste 53 or materials 54 , 55 , or with different percentages of moisture. Still others have modified other parameters such as die height, Lisowski et al (2019) 56 and have verified how the moisture of the matrix can be determined in the pelletizing process.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the Izod impact test (Type A), V-shaped notches were made by using NOTCHVIS (CEAST) for the five replicate specimens of each sample having the dimensions of 70 mm × 15 mm × 3 mm as per the ASTM D256 (2010) standard [46,47] through Gotech GT-7045-MD (Taichung City, Taiwan). The notch angle had a 45° radius and the notch depth was 2.5 mm.…”
Section: Characterizationsmentioning
confidence: 99%
“…The authors conclude that SCG must have a surface treatment in order to improve the interfacial adhesion with the matrix and to improve the tensile strength for future works. These composites, based on SCG and PP homopolymer, could be used as substitutes for virgin PP in some applications, where the impact strength and the sustainable principles are needed [ 16 ].…”
Section: Scg Polymer Compositesmentioning
confidence: 99%
“…The residues of SCG can be directly used as fillers in composites (mainly polymer matrices), or after chemical modifications (the extraction of the molecules of interest). Typical examples of polymer matrices are synthetic polymers, such as polyurethane [ 15 ] and polypropylene [ 16 , 17 , 18 ], or biopolymers, such as polylactic acid (PLA) [ 19 , 20 , 21 ]. The resulting materials have been proposed for various applications, such as for packaging (mostly food), disposable products (single-use products/composting), and 3D printing [ 15 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%